Pengaruh Modal Kerja, Likuiditas, Umur Perusahaan dan Pertumbuhan Perusahaan terhadap Profitabilitas; Studi Kasus pada Perusahaan Food and Beverage yang terdaftar di BEI Tahun 2014-2018 - Dwi Kristanti, Nucke; Wiyono, Gendro; Prima Sari, Pristin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Food and beverage companies are industrial companies involved in managing the food and beverage industry and play an important role in Indonesia's economic growth. Every business tries to achieve optimal profit or profit in continuing its business in the future. The purpose of this research is to analyze the effect of working capital, liquidity, company age and company growth on profitability. In this study the number of population is 41. Target sampling, the technique used with certain criteria. Samples were obtained from 16 sample companies. Descriptive statistical panel data and regression using SPSS 2.1 software are used as data analysis techniques. As a data processing tool for presenting statistical data Based on the results of the study it was stated that the working capital variable had a positive and significant effect on profitability, while the liquidity variable was assumed to have a positive effect on profitability, while the company expectation variable was assumed to have a positive effect on profitability, and the company growth variable was assumed to have a positive effect on profitability profitability. From this it can be concluded that the variables of working capital, solvency, firm age together influence profitability.